Intra-Aortic Balloon Pump Rupture and Entrapment - Artan Jahollari; Atilla Sarac; Ertugrul Ozal (Case Reports in Vascular Medicine)
Intra-aortic balloon pump is used frequently to support a failing myocardium in cardiac patients. Due to the invasive nature of this device, usage is accompanied by consistent risk of complications. Balloon rupture, although it occurs rarely, may lead to entrapment if diagnosis delays. A 78-year male who underwent cardiac surgery experienced balloon rupture and entrapment in the right femoral artery during the postoperative follow-up. Surgical extraction under local anesthesia was performed and the patient had an uneventful course. Fast and gentle solution of the problem is necessary to prevent further morbidity or mortality related to a retained balloon catheter in these delicate patients.